The Infection Control Risk Assessment and Strategies to Reduce HAIs at Hospital in Yogyakarta Indonesia - Elsye Maria Rosa; Ekorini Listiowati; Nurmalita Sari (Asian Social Work Journal, 2019)
Identifying the problem of infection is needed to analyze risk management. One of the tools to manage the risk of Hospital-Acquired Infections (HAIs) is by using the ICRA (Infection Control Risk Assessment). Arranging a risk assessment of infection control is essential to prevent the potential incidence of infection that is not expected. This research analyzes the Infection Control Risk Assessment and reduction strategies of Health-Care-Associated Infections at Hospital in Yogyakarta . The type of analysis was descriptive qualitative with case study approach. The researcher used informants who were involved in the implementation of the prevention and infection with the data control. The researcher also collected data using depth interviews and documents reviews. Risk management process, the findings of risk identification (1) the transmission of infectious diseases, microorganisms through direct and indirect contact, (2) infection, (3) the duration of treatment, delayed homecoming, disability, (4) healthcare workers, patients, visitors, and hospital environments. The highest risk assessment was surgical site infection. The HAIs reduction strategies were taken by breaking the chain of infection, bacterial identifying using HAIs, using the rational antibiotic, optimizing surveillance of HAIs, implementing periodic regular meetings, reporting, cooperating, evaluating, socializing, monitoring and preventing, the reinvigorating the SOP for the type of HAIs. The advice for the management of Hospital is that they need to notice more on the implementation process of the prevention and infection control.